ANSWER and EXPLANATION
We are given a function and its inverse function:
![\begin{gathered} f(x)=(1)/(2)x \\ f^(-1)(x)=2x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o1g2krnym6ku8cr1cfbr7v4007214aolex.png)
To solve the problems, we have to substitute the values of x in the brackets into the appropriate function (or inverse function).
Therefore, we have that the value of the function for x = 2:
![\begin{gathered} f(2)=(1)/(2)\cdot2 \\ f(2)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wgchut281rd1ql05c0xeozdjk6d6zte1sk.png)
For x = 1, we have that the value of the inverse function is:
![\begin{gathered} f^(-1)(1)=2(1) \\ f^(-1)(1)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pq3rmphrn797zljevol06vj3f4yn3yq93y.png)
For x = -2, we have that the value of the inverse function is:
![\begin{gathered} f^(-1)(-2)=2\cdot-2 \\ f^(-1)(-2)=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n688gkols2arbfxz8dkxnpk8lvlhw2f5tw.png)
For x = -4, we have that the value of the function is:
![\begin{gathered} f(-4)=(1)/(2)\cdot-4 \\ f(-4)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rp9cre7ydfvietoatnzm4xg3447bxvbiam.png)
For the fifth option, substitute the value of the function at x = 2 into the inverse function.
That is:
![\begin{gathered} f^(-1)(f(2))=f^(-1)(1)=2\cdot1 \\ f^(-1)(f(2))=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/akrv8qraaprirk2e1rzw4u6a80vmd4iuh4.png)
For the sixth option, substitute the value of the inverse function at x = -2 into the function.
That is:
![\begin{gathered} f(f^(-1)(-2))=f(-4)=(1)/(2)\cdot-4 \\ f(f^(-1)(-2))=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7gmbf3cto1q084dcsy3wlgfvpfpa5qs20w.png)
To find the general form of the function:
![f^(-1)(f(x))=f(f^(-1)(x))](https://img.qammunity.org/2023/formulas/mathematics/college/bqrckjvzb6812ys6y2rx2114ncr2lyp25z.png)
either substitute the function for x in the inverse function or substitute the inverse function for x in the function.
Therefore:
![\begin{gathered} f^(-1)(f(x))=2((1)/(2)x)) \\ f^(-1)(f(x))=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hsce0tthux7itod5c31bi3y4u1hlz1u0qv.png)
That is the answer.